Ulama Dalam Temuan Arkeologi Islam - Ahmad Cholid Sodrie (Balai Arkeologi Yogyakarta, 1995)
Java and Aceh is an area of growth and development of Islam in Indonesia. In Java the scholars are known as the Guardians (Wali Sanga = 9 Guardians of God) such as Sunan Gunung Jati for the region of West Java; Sunan Kali Jaga for Central Java; and Sunan Giri for East Java. As for Aceh known names Hamzah Fansuri, Samsudin as-Sumatrani and Nuruddin ar-Raniri. But it does not rule out the possibility that other areas in Indonesia there are scholars. Remains of manuscripts in Aceh spread all over, especially in places where regeneration ummah (Zawiyah or Ule in Aceh, or pesantren).